Permeability and pore structure of microcapsule-based self-healing cementitious composite. (20th March 2018) - Wang, X.F.; Zhang, J.H.; Zhao, W.; Han, R.; Han, N.X.; Xing, F.
Highlights: Studied permeability of self-healing cementitious composites, including pore structure. Small amounts of microcapsules positively affect pore structure and impermeability. Self-healing efficiency increases with increasing microcapsule content and particle size. Series relationships were obtained to predict relationship of impermeability vs. pore structure parameters. Abstract: The effects of adding organic microcapsules having various particle sizes and composition on the permeability, carbonation resistance, pore structure, and self-healing efficiency of cementitious composite material were studied using rapid chloride migration, water pressure penetration, carbonation, and mercury intrusion porosimetry tests. It was found that increasing microcapsule content to 3% improved pore structure and impermeability. However, with 6% microcapsule content, the material impermeability became even lower than that of a specimen without microcapsules. The variation of particle sizes had a slight negative impact on impermeability although it improved pore structure. Increasing microcapsule content and particle size enhanced impermeability, pore structure, and self-healing efficiency of specimens.